DESCRIPTION OF NEW SPECIES OF KLEIDOTOMA WESTWOOD (HYMENOPTERA: FIGITIDAE) FROM INDIA ALONG WITH A LIST OF SPECIES - AKHTAR, MIR SAMIM; AKHTAR, MIR SAMIM; KUMAR SINGH, LONGJAM RONI; V. V. RAMAMURTHY; KHAN, FARMANUR RAHMAN (The Bioscan, 2013)
The genus Kleidotoma is reported for the first time from India with Kleidotoma sikkimensis sp. nov. Akhtar. The new species is described from Sikkim, India and distinguished from K. kraussi Yoshimoto through malar space about 0.32x height of eye, scape 1.66x as long as broad, pronotum behind plate on each side with about 2 costate extending somewhat diagonal to margin of mesoscutum, radial cell moderate in size, apical portion of radial vein not extending beyond radial cell along the wing margin, scutellar cup not extending to the apex of the disc. A list of Kleidotoma is given which includes 119 species, of this 74 species from Palearctic, 16 species from Afrotropical, 4 species from Neotropic, 2 species from Oriental, 1 species each from Antarctic and Australasian, 18 species from Nearctic + Neotropic, 1 species each from Palearctic + Australasian and Palearctic + Neotropic and 1 species from Neotropic + Australasian + Nearctic region along with synonyms and distributions.